2021
DOI: 10.1016/j.intimp.2021.108127
|View full text |Cite|
|
Sign up to set email alerts
|

Forecasting of Oxidant/Antioxidant levels of COVID-19 patients by using Expert models with biomarkers used in the Diagnosis/Prognosis of COVID-19

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 47 publications
1
28
1
Order By: Relevance
“…The new severe acute respiratory syndrome coronavirus (SARS-CoV-2), first identified in 2019, has rapidly affected the world and caused a pandemic [1,2]. The disease, identified as coronavirus 2019 (COVID- 19), can cause severe pneumonia and fatal acute respiratory distress syndrome (ARDS) [3][4][5][6]. While the disease may be asymptomatic, severe ARDS is thought to be caused by an inflammatory cytokine storm that may be encountered during the disease period [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The new severe acute respiratory syndrome coronavirus (SARS-CoV-2), first identified in 2019, has rapidly affected the world and caused a pandemic [1,2]. The disease, identified as coronavirus 2019 (COVID- 19), can cause severe pneumonia and fatal acute respiratory distress syndrome (ARDS) [3][4][5][6]. While the disease may be asymptomatic, severe ARDS is thought to be caused by an inflammatory cytokine storm that may be encountered during the disease period [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the clinical importance of changes in routine blood parameters (RBV) in the diagnosis and prediction of prognosis of infectious diseases [1][2][3][4][10][11][12]. Similarly, many abnormalities have been reported in the peripheral blood of patients infected with COVID-19 [6,7,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the change in routine blood parameters has certain clinical application value in predicting the progression of infectious diseases [ [1] , [10] , [37] ]. Indeed, many abnormalities have been reported in the peripheral blood of some infected patients [2] , [6] , [9] , [11] .…”
Section: Introductionmentioning
confidence: 99%
“…However, information on the early predictive indicators for particularly severe and fatal cases is relatively limited and further research is needed [ [9] , [37] ]. In addition, the rapid spread of the disease raises concerns about the need for intensive care that can overwhelm health care system resources [13] .…”
Section: Introductionmentioning
confidence: 99%